Essential oils from Cordia verbenacea and Elionurus latiflorus and their binary mixture: Bioactivity against the Mexican bean weevil and an aflatoxin-producing fungal species - Faria, Rodrigo Donizeti [UNESP]; Cabral, Isabela Rubio [UNESP]; dos Santos Oliveira, Thaís Aparecida; Thiesen, Leonardo Vinicius; Rakes, Matheus; Nesi, Cristiano Nunes; Raetano, Carlos Gilberto [UNESP]; da Glória, Eduardo Micotti; Crotti, Antônio Eduardo Miller; do Prado Ribeiro, Leandro (Elsevier, 2023)
Chemically diversified essential oils (EOs) have a broad spectrum of biological activities, so they are promising sources of compounds with simultaneous action on stored-grain spoilers. This study has evaluated the insecticidal action and behavioral effects of the EOs obtained from Cordia verbenacea (Boraginaceae) and Elionorus latiflorus (Poaceae) leaves, tested in isolation or as binary mixture (1:1, v v-1), against the Mexican bean weevil, Zabrotes subfasciatus (Coleoptera: Chrysomelidae), a primary pest of stored beans in tropical regions. This study has also evaluated the antifungal and antiaflatoxigenic properties of these EOs against Aspergillus nomius (Ascomycota), which produces aflatoxins B1, B2, G1, and G2. GC-MS analyses indicated that sesquiterpene hydrocarbons (86.5%) and oxygenated monoterpenes (95.7%) predominated in the EOs obtained from C. verbenacea and E. latiflorus leaves, respectively. Both EOs and their binary mixture were toxic to Z. subfasciatus adults in fumigation, residual contact, and topical application trials; the EO obtained from E. latiflorus leaves was the most potent. In addition, computational behavioral tracking showed that the distance covered by females exposed to the EO obtained from E. latiflorus leaves at the previously estimated LC50 was significantly reduced. Analysis of isobolograms indicated that the binary mixture of the EOs had an additive effect for both the residual contact and topical application exposure modes, while antagonism was verified for fumigation. The EO obtained from E. latiflorus leaves and the binary mixture also inhibited radial growth and production of aflatoxins B1, B2, G1, and G2 in a concentration-dependent manner. Thus, the tested EOs, especially from E. latiflorus, are promising grain-protectants with multiple actions against grain spoilers.
Keywords: Binary mixture; Biological activities; Grain spoilers; Walking behavior; “Baleeira herb”; “Brazilian lemongrass”